Handbook of Evidence-Based Radiation Oncology (Springer International Publishing, 2018)
The Third Edition of Handbook of Evidence-Based Radiation Oncology updates and revises the previous successful editions and serves as a key reference for radiation oncology professionals. Organized by body site, concise clinical chapters provide easy access to critical information. Important "pearls" of epidemiology, anatomy, pathology, and clinical presentation are highlighted. The key elements of the work-up are listed, followed by staging and/or risk classification systems. Treatment recommendations are discussed based on stage, histology, and/or risk classification. Brief summaries of key trials and studies provide the rationale for the recommendations. Practical guidelines for radiation techniques are described and complications and follow-up guidelines are outlined. The Third Edition incorporates new key studies and trials to reflect current radiation oncology practice; includes the most recent staging systems; and features new color illustrations and anatomic atlases to aid in treatment planning. This book is a valuable resource for students, resident physicians, fellows, and other practitioners of radiation oncology. .